ASUHAN KEPERAWATAN PADA TN. S DENGAN PENERAPAN FOOT ELEVATION TERHADAP PENURUNAN DERAJAT EDEMA PADA PASIEN CONGESTIVE HEART FAILURE DI RSUD ARIFIN ACHMAD PEKANBARU - Intan Zanisa; Yenny Safitri; Rian; Dewi Sulastri Juwita (El-Emir Institute, 2025)
Congestive Heart Failure (CHF) is a major risk factor for leg edema. Edema can occur because blood accumulates in the feet, ankles and soles of the feet. The aim of this research is to determine the effect of 30° foot elevation on reducing the degree of lower extremity edema in Mr. S, who was medically diagnosed with Congestive Heart Failure (CHF), in the Krisan Room of Arifin Achmad Hospital, Pekanbaru, in 2025. This research is a quasi-experimental study conducted from May 15–17, 2025, with a sample of 1 respondent at Arifin Achmad Hospital, Pekanbaru. The results showed that the administration of 30° foot elevation had an effect in nursing care for Mr. S to reduce lower extremity edema, namely reducing from edema grade 3 to edema grade 2. Recommendation: It is expected that clients and families will always pay attention to their health condition and perform independent care by using 30° foot elevation if edema occurs.